Optical coherence angiography: A review. Issue 41 (October 2016) - Wylęgała, Adam; Teper, Sławomir; Dobrowolski, Dariusz; Wylęgała, Edward
Abstract: Background: Retinal vascular diseases are one of the most common causes of blindness in the developed world. Optical Coherence Tomography Angiography (OCT-A) is a new noninvasive method that uses several algorithms to detect blood movement. This enables the creation of high-resolution vascular images with contrast depicting motionless tissue. Methods: This review presents the results of articles relevant to age-related macular degeneration (AMD), diabetic retinopathy (DR), and OCT-A. The OCT-A technique can successfully be used in the diagnosis of neovascularization, retinal vein occlusion (RVO) and retinal artery occlusion (RAO), vessel abnormalities and even anterior segment neovascularization. OCT-A can also be applied to compute data such as vessel density, and flow index in both superficial and deep plexuses. Results: Many studies have compared fluorescein angiography with OCT-A. Other studies have reported differences in vascular density in AMD patients and have compared them with people having healthy eyes. Although OCT-A offers rapid picture acquisition, high repeatability and resolution, it also has many drawbacks. The most common are: motion artifacts, projections from overlying vessels and limited field of view. An interesting new application is the possibility to assess changes during antivascular endothelial growth factor (anti-VEGF) therapy. Another function of OCT-A is the possible application in the study of choriocapillaries in many fields of ocular pathology. Conclusion: OCT-A is a new promising method that allows the visualization of the retinal vascular network and the counting of blood flow parameters. This technique provides reliable images useful in clinical routines.